Effects of diets on structure and population size of Apocyclops royi (Copepoda: Cyclopoida) - Phung, Khanh Chuyen; Tran, Ngoc-Son; Pham, Thi Phuong; Trinh-Dang, Mau (Hue University Journal of Science: Natural Science, 2025)
This paper investigates the effects of different diets on the growth and development of Apocyclops royi (A. royi) in the laboratory. A. royi individuals were acclimatised in a laboratory culture environment, and newly hatched larvae of the same age were collected and raised until adulthood for the experiment. Different diets were arranged and evaluated to select the optimal food for the growth and development of A. royi. The experiments included the following treatments: the green alga Chlorella vulgaris (C. vulgaris), microbially fermented rice bran combined with C. vulgaris algae, and yeast combined with C. vulgaris algae. The results show that the diet containing microbially fermented rice bran combined with C. vulgaris algae yielded the best performance for the A. royi population, evidenced by the highest density of 9,022.22 ± 1,066 ind·L–1 at day 12 and the highest larval yield compared with the other treatments (p < 0.05). This study provided a scientific foundation for selecting the optimal diet to enhance the biomass production efficiency of copepods, a nutrient-rich natural food source for fish and marine crustacean larvae. Consequently, it contributed to the optimisation of the food chain in sustainable aquaculture.